2019
DOI: 10.2478/ata-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Comparison of Different Photovoltaic Modules

Abstract: Solar photovoltaic power generation capacity is rising continuously as a result of various regional, sub-regional renewable energy policies and the impact of technology development, as well as the increasing environmental concerns. Characteristics of photovoltaic modules are provided by manufacturers after they have been tested indoors under standard test conditions. These parameters may vary under exterior conditions. It is thus imperative to establish the quantity of the energy produced by photovoltaic modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Final mathematical description of polynomial graphical dependencies was obtained after application of fitting procedure and regression analysis. (Kafui et al, 2018) and practice have proved that heat can affect the performance of solar modules and shorten their lifespans.…”
Section: The Influence Of Selected External Factors On Temperature Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Final mathematical description of polynomial graphical dependencies was obtained after application of fitting procedure and regression analysis. (Kafui et al, 2018) and practice have proved that heat can affect the performance of solar modules and shorten their lifespans.…”
Section: The Influence Of Selected External Factors On Temperature Ofmentioning
confidence: 99%
“…All aforementioned conditions have a significant influence on PV cell energy production; however, the most crucial factor is temperature. The effects of the PV module operating temperature on the output efficiency have been described by Jones andUnderwood (2001), Schott (1985), Servant (1985), Kafui et al (2018) and their research results have shown that increasing temperature has a negative impact on the amount of power available. On the basis of the presented facts, the paper Acta Technologica Agriculturae 4 Nitra, Slovaca Universitas Agriculturae Nitriae, 2019, pp.…”
mentioning
confidence: 99%
“…This could lead to better on-track results and will provide opportunity for higher ranking in the next Shell Eco Marathon competitions. Additionally, the vehicle can be further improved with the addition of different energy harvesting solutions, like a photovoltaic system with solar panels (Kafui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…5a and 5b represented, module efficiency value of different PV modules (thin plate Copper indium diselenide, polycrystalline silicon, mono-crystalline silicon, micro crystalline silicone and amorphous silicon) for whole year. It is examined that module efficiency of different types of PV modules are directly linked with maximum power output and inversely related with module temperature [43,[68][69][70].…”
Section: Module Efficiency Analysismentioning
confidence: 99%